An exploration into the knowledge, understanding and management of the female athlete triad and the triad risk factors among elite swimmers in KwaZulu-Natal (KZN) - Seals, E. (Durban University of Technology, 2022)
Background: The Female Athlete Triad (FAT) includes a spectrum of dysfunction referring specifically to three health complications, which primarily are energy deficiency, menstrual disturbances, and low bone mineral density. Women`s participation in sport has drastically increased over the last four decades but women are still facing stereotyping and are often expected to look a certain way, on and off the sporting grounds. The female athlete triad is common and is widely researched in land sports, such as athletics and endurance running, but the majority of the studies focus on the prevalence of the condition, instead of its knowledge and/or management. Despite FAT being widely researched in various sporting disciplines, there was an apparent gap in the literature, and especially under investigated in elite swimmers. Despite swimming being a popular endurance-type discipline, with similar outcomes to land sporting disciplines, there is paucity in the current literature on FAT in swimmers in South Africa. The benefits of understanding the knowledge of FAT in an elite swimmer includes optimizing energy availability by ensuring adequate caloric intake whilst exercising, encouraging regular weight bearing exercise, improving the triad`s identification, and preventing its occurrence. Aim of the study: The aim of this study was to explore the knowledge, understanding and management of FAT and the triad risk factors among elite swimmers in KwaZuluNatal (KZN). Methodology: A qualitative, exploratory, descriptive approach was used to guide the study. A semistructured interview guide was used to conduct in-depth interviews with nine elite female swimmers in KwaZulu-Natal (KZN). The main research questions for this study were "Describe your understanding of the female athlete triad", "Can you expand/elaborate on what makes an individual at risk for the triad?" and "Describe the management options that you, or someone that you know that has had FAT used". The data were analysed using Tesch`s (Creswell 2007) method to identify themes and sub-themes. Results: The main themes that emerged from the study were the lack of knowledge on the female athlete triad, the understanding of the female athlete triad risk factors, the understanding of the impact of fat on health and performance, the lack of education surrounding the management of FAT and the lack in choice of healthcare. The participants had poor knowledge of the term the Female Athlete Triad however, the understanding of the triad risk factors was well understood. Participants in this study lacked appropriate choices in healthcare, if they were to have been presented with components of the triad. Conclusion: The findings that emerged from this study indicate that there is a lack of knowledge and understanding surrounding the female athlete triad, its associated risk factors and the appropriate management interventions needed if an athlete were to be diagnosed with FAT. Therefore, it is necessary for not only the chiropractic community but for all health practitioners who may deal with elite female athletes to educate and inform this population about the potential long term health consequences of FAT.